Climate change–drylands–food security nexus in Africa: From the perspective of technical advances, challenges, and opportunities - Hirwa, Hubert; Li, Fadong; Qiao, Yunfeng; Measho, Simon; Muhirwa, Fabien; Tian, Chao; Leng, Peifang; Ingabire, Romaine; Itangishaka, Auguste Cesar; Chen, Gang; Turyasingura, Benson (Frontiers in Environmental Science, 2022)
Climate change impacts on drylands pose more vexing risks to socio-ecological systems, resulting in food security issues, biodiversity loss, and livelihood shifts in Africa. This study critically reviewed relevant literatures to evaluate the complexities and feedback loops between the climate-drylands-food security (CDF) nexus, which help assess tactics to attain sustainable dryland ecosystem management under the changing environment. Comprehensive CDF frameworks are explored for dryland dynamics, ecosystem services, and food security (FS) and current high-precision ecosystem observation networks are used to detect regional level climate variability and identify hotspots. Besides, this review also examines challenges and uncertainties for CDF systems and effective agrarian innovations as a way forward. To bridge the gap from science to policy-making in the CDF nexus, it is vital to enhance the impacts and feedbacks of ecohydrological processes on agrarian production, ecosystem services tradeoffs, and their effects on livelihoods, and regional development and preservation by under optimization of ecological water security pattern. This state-of-the-art assessment uses acquired information and knowledge to conceptually evaluate the past, current, and future impacts and risks, and facilitates decision-making through the delivery of long-term sustainability and socio-ecological resilience.